Socio-educational intervention program for the smoking prevention in dentistry students - Miguel Ángel Toledo Méndez; Midiala Veloz Fariñas; Tania Quesada Rabelo; Yanexis Valdés Gárciga; José Carlos Toledo Quirós (Medisur)
Foundation: smoking represents one of the main public health problems. Its high frequency in the youth stage is especially worrying. Objective: to propose a socio-educational intervention program for dentistry students smoking prevention. Methods: descriptive study that included a non-probabilistic sample of 75 smoking and non-smoking students from the dentistry program at the Villa Clara Medical Sciences University. The following analyzed variables were: age, sex, academic year, origin, duration of smoking, number of cigarettes per day, level of dependence and attitude regarding consumption. From this, an educational intervention program was designed, which was evaluated by expert criteria. Results: there was a predominance of young smokers with an extended practice between three and five years, in whom moderate dependence was confirmed. The proposed socio-educational intervention program contains the objectives to be achieved, the strategies to be put into practice, the resources to be used and the planned timing. The evaluation of the program through expert criteria showed its applicability and viability. Conclusions: the proposed socio-educational intervention program assumes as a distinctive feature the prevention of smoking through phases or stages that interrelate axes, activities and tasks, such as spaces or areas of action located at the individual and group level.